PENGARUH ACADEMIC HARDINESS DAN RESILIENSI AKADEMIK TERHADAP WORK READINESS PADA MAHASISWA BIMBINGAN DAN KONSELING - agestya miftahiyatul; Tri Sutanti; Agus Ria Kumara; Aprilia Setyowati (IKIP Siliwangi, 2026)
Work readines is a important aspect in higher education because it reflects students’ readiness to face increasingly complex academic and professional demands, especially for Guidance and Counseling Study Program students. Work readines is not only determined by mastery of technical competencies, but also by internal psychological factors such as academic hardiness and academic resilience on work readines in Guidance and Counseling students. This study uses a quantitative approach with a correlational design. The population of this study includes 537 Guidance and Counseling students, the number of samples in this study is 172 students in the 1st and 3rd semesters ages 18 – 21 years, selected through a purposive sampling technique. The data analysis technique uses the nonparametric Spearman Rank Order corellation test (Spearman’s Rho) because the data does not meet the assumption of normality. The result of the Spearman’s Rho analysis indicate that thetre is a signicant influence between academic hardiness and academic resilience on work readines. These findings indicate that students with academic resilience abd good adaptability to academic preassure tent to have optimal work readines, so that academic hardiness and academic resilience can be understood as important psyological factors of Guidance and Counseling students.